OPTIMIZING DRIVE OF HYBRID VEHICLE WITH INOPERATIVE ENGINE OF INTERNAL COMBUSTION - Mokin, O. B.; Mokin, B. I.; Lobatiuk, V. A.; Kubrak, O. P. (Visnyk of Vinnytsia Politechnical Institute, 2015)
There has been solved the problem optimization of motion of the vehicle with a combined drive of the internal combustion engine and the electric motor of a direct current path that includes in addition to the horizontal sections also the descents and climbs, and the movement is carried out only with the electric system when the engine of internal combustion is switched off.